Pola Kemitraan Jaringan Sosial Swadiri Bali (JSSB) dengan Petani (Bina Karya Mandiri) dalam Penyaluran Bantuan dari Pemerintah - MARDIKA, K REDIK; WINDIA, I WAYAN; PARINING, NYOMAN (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2019)
The Partnership Pattern of the Bali Self-Social Network ‘Jaringan Sosial Swadiri Bali’ (JSSB) and Farmers (Bina Karya Mandiri) in the Distribution of the Grant Provided by the Government The government provides different types of grant to the farmers; however, this does not mean that the farmers always have immediate access to them. There are many requirements which should be fulfilled by the farmers. The Bali Self-Social Network ‘Jaringan Sosial Swadiri Bali (JSSB) helps the group of farmers referred to as Bina Karya Mandiri obtain the grant provided by the government through the pattern of partnership. This current study was intended to identify the mechanism, the rights and obligations, and the obstructions which the partnership between JSSB and the farmers (Bina KaryaMandiri) faces in the distribution of the grant provided by the government. The samples of the current study were determined using the sampling purposive technique. The data were collected through in-depth interview, rapid rural appraisal, library research and documentary methods. Then the data were qualitatively analyzed. It could be concluded from the study that JSSB prepares production facilities, production technological guidance and supervision as to where to market the products and Bina Karya Mandiri prepares land and manpower to support the production process. In the partnership JSSB is not entitled to the benefit obtained by Bina Karya Mandiri; however, it is entitled to supervising the activities done byBina Karya Mandiri. Bina Karya Mandiri is entitled to having the production facilities fixed, and Bina Karya Mandiri is obliged to report the development of the group every month. The problem is that the group’s members are getting less interested in doing the group’s activities. It will be better if the group’s members maintain the partnership between Bina Karya Mandiri and JSSB as it benefits them.